G201(P) An audit of endotracheal intubation outcomes relative to trainee level. (7th April 2014) - Jamieson, K; Armour-Marshall, J; Birley, K; Leith, W
Abstract : Objectives: We hypothesise that endotracheal intubation success and adverse incidents are related to the level of the trainee performing the intubation. Method: Retrospective analysis of primary intubations performed by a level 2 neonatal unit over 18 months. Patients were identified using SEND summary coding and checking against records of intubation drug use. Data collected included gestation, weight, indication for intubation and influencing factors, such as administration of sedation and patient co-morbidities. Outcome measures included first attempt success, overall success by initial provider and associated adverse outcomes. Results: 68 intubations were performed, 16 on NICU as semi-elective procedures, 52 as emergency procedures without medication. Initial providers were successful on the first attempt in 38% and overall in 75%, sub-divided by grade as follows: See Table 1 Initial providers were successful on the first attempt in 33% on labour ward, compared to 56% on NICU: See Table 2 Minor adverse incidents occurred in 10 cases (20% SHO, 50% SpR, 30% grade not recorded, 0% Consultant). No severe incidents occurred. Conclusion: First attempt success is generally low, more so in emergency situations. Overall success improves with higher training grades. Severe adverse incidents are rare, but minor incidents (e.g. tube dislodging) are common. Intubation is a key skill in the stabilisation of premature or unwell neonates. With changes in working hours, and the increasing use of non-invasive ventilation, trainees have less exposure to intubation. This study demonstrates the need for innovative approaches to training in intubation that enhance trainee experience.